Efeitos da exposição crônica ao estresse de derrota social sobre os efeitos estimulantes e reforçadores do etanol - Macedo, Giovana Camila de [UNIFESP] (2017)
Repeated exposure to ethanol and other drugs of abuse promotes neuroadaptations on brain reward systems, rendering them hyper responsive (i.e., sensitized) to drugs. The sensitization of brain reward responses to drugs would, in turn, facilitate drug-induced stimulation and reward. Likewise, repeated exposure to episodic stress seems to sensitize brain reward pathways, promoting cross-sensitization with drugs and increased drug intake. In contrast, exposure to continuous stress may induce an anhedonic state associated with the reduction of drug reward. To assess whether repeated exposure to two types of social stress induces cross-sensitization to the stimulant effect of ethanol and promotes increased voluntary ethanol consumption. The association between behavioral sensitization induced by repeated ethanol treatment and voluntary drinking was also tested. Swiss male mice were exposed to two types of social defeat stress (episodic vs. continuous) during 10 days, and 10 days later were challenged with a stimulant dose of ethanol (2.2 g/kg or 1.6 g/kg, ip). Next, we evaluated the voluntary intake of ethanol solutions (6%, 10% and 20% w / v) with two-bottle choice, home cage drinking sessions of 24h, every other day. Another group of animals was exposed to 10 days of repeated treatment with ethanol (2.2 g/kg, i.p.) as a positive control of sensitization, and was evaluated for voluntary ethanol drinking. Repeated exposure to 10 days of continuous social defeat promoted insensitivity to the stimulating effect of ethanol, while episodic defeat had no effects. Pre-exposure to episodic or continuous defeat stress failed to affect voluntary ethanol drinking. On the other hand, a 10-day treatment with ethanol injections induced behavioral sensitization to ethanol-stimulation and increased ethanol intake in concentrations of 10%. These findings indicate that repeated exposure to episodic social stress did not escalate ethanol drinking, nor induced cross-sensitization. Animals exposed to continuous defeat stress showed a blunted stimulant response to ethanol, but no changes in intake. On the other hand, we provided support for a positive association between ethanol-induced behavioral sensitization and ethanol drinking.